Gastric Cancer Presenting as Isolated Ascites: A Diagnostic Challenge - Duarte, Inês (Eur J Case Rep Intern Med, 2019)
Malignant ascites is a rare first manifestation of gastric carcinoma and is usually associated with symptoms which include early satiety, abdominal pain and deteriorating clinical state. The authors describe the case of a male patient presenting with malignant ascites of rapid onset which was the sole presentation of gastric cancer, highlighting the importance of upper gastric endoscopy even in the absence of gastrointestinal symptoms. LEARNING POINTS: Malignant ascites is present in 10% of cancer patients and is associated with a poor prognosis. Gastric cancer causes malignant ascites in 18% of cases but is rarely the first symptom. As the absence of lesions on a full body CT scan does not exclude gastric cancer, gastrointestinal endoscopy is still the best diagnostic test.